2008
DOI: 10.1038/sj.bjp.0707578
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐dependent accumulation of leukocytes in sinusoids mediates hepatocellular damage in bile duct ligation‐induced cholestasis

Abstract: Background: Although it is well known that extrahepatic cholestasis induces liver damage, the mechanisms are still not completely understood. The aim of the present study was to evaluate the role of platelets and P-selectin in cholestasis-induced liver injury. Experimental approach: C57BL/6 mice underwent bile duct ligation (BDL) and pretreatment with an anti-GP1ba antibody, which depletes platelets, an anti-P-selectin antibody or a control antibody. Hepatic platelet and leukocyte recruitment as well as microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 30 publications
6
66
0
Order By: Relevance
“…Indeed, in experimental settings where neutrophils are definitively linked to hepatotoxicity, the interaction of platelets and neutrophils worsens liver damage. [46][47][48] We found that platelet depletion tended to reduce accumulation of neutrophils within necrotic foci in APAP-treated mice. It is worth noting, however, that the role of neutrophils in APAP hepatotoxicity continues to be debated.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, in experimental settings where neutrophils are definitively linked to hepatotoxicity, the interaction of platelets and neutrophils worsens liver damage. [46][47][48] We found that platelet depletion tended to reduce accumulation of neutrophils within necrotic foci in APAP-treated mice. It is worth noting, however, that the role of neutrophils in APAP hepatotoxicity continues to be debated.…”
Section: Discussionmentioning
confidence: 75%
“…Nicotinamide adenine dinucleotide phosphate oxidase 2 might also play a role in mediating platelet-neutrophil interactions in this setting (61). In another sterile injury model, following bile duct ligation-induced cholestasis, platelet aggregates support leukocyte recruitment to liver sinusoids and postsinusoidal venules involving P-selectin (63). Hence, these studies emphasise a mechanistic link between platelet-leukocyte interactions and leukocyte recruitment followed by tissue damage in a wide range of inflammatory liver disease.…”
Section: Platelet-leukocyte Interactions In Pathologic Conditionsmentioning
confidence: 99%
“…Given the number and variety of bioactive substances secreted by platelets (Table 1), it is unsurprising that they have been implicated in the development or severity of an array of disorders (Table 2) [11,[24][25][26][27][28][29][30][31][32][33][34][35][36]. Some of these disorders may appear obvious (thrombosis and restenosis) but others may not (psoriasis and migraine).…”
Section: Disorders Involving Local and Systemic Platelet Activationmentioning
confidence: 99%